Microwave pulse compression using helically corrugated waveguides - Young, A; Ronald, K; MacInnes, P; Whyte, C; Burt, G; He, W; Konoplev, I; Phelps, A; Cross, A; Samsonov, S; Bratman, V; Denisov, G; et al. (2006)
Cylindrical waveguide with a helical corrugation on the inner surface has proven an effective dispersive medium for the compression of smoothly frequency modulated microwave pulses. This paper presents the results of experiments where ∼5.6kW, X-band (S.0GHz to 12.5GHz), microwave pulses of 80ns duration and 5% frequency modulation were compressed into 1.5ns pulses with 25 times higher peak power. © 2006 IEEE.